SISTEM PENUNJANG KEPUTUSAN KENAIKAN JABATAN KARYAWAN DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Kefas Oswald Mokirimban; Herwana; Sitti Arni (PROGRESS, 2022)
PT. United Tractors is a company engaged in the distribution of heavy equipment, but the current problem that is often the main focus for employees regarding promotions at PT. United Tractors, which often appears as a result of measuring tools in the process of increasing positions, still seems manual which is assessed directly by the company's leadership, especially in measuring work performance, performance and discipline. This study aims to facilitate the leadership and speed up the selection process for employee promotions using the Analytical Hierarchy Process (AHP) method. The final result of this research is to create a web-based application system that is used as a decision support system for employee promotions using the Analytical Hierarchy Process (AHP) method, easy to implement and can be calculated by the system using predetermined criteria and weights.